TV Broadcast Piracy Through Illegal Live Streaming Applications: Challenges and Legal Protection for Copyright Holders - Tan, Winsherly; Situmeang, Ampuan; Bhaskara, Kevin Indra (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2024)
The copyright infringement that is currently on the rise is the emergence of illegal TV streaming apps. The application is now very annoying to official broadcasting rights holders because the presence of such illegal streaming applications will cause losses. This paper aims to find out the form of legal protection as well as legal action for television stations that suffer losses from the piracy of such broadcasting activities.This study is a normative legal study with normative jurisprudence approach to critically analyse the criminal and civil law norms against piracy TV broadcasts through the Live Streaming application aimed at digging and revealing the protection and enforcement of the law for TV stations suffered losses as a result of such piracy.If a person is found to conduct broadcasting or distribution without the permission of the owner who violates the provisions of Article 25 paragraph (2) of the Copyright Act with the criminal punishment of Article 118 of the copyright Act. Whereas the perpetrator of illegal live streaming application that violates Article 32 paragraph (1) of the ITE Act, can be subject to criminal sanctions as referred to in Article 48 paragraph 1 of the Act. The resolution of copyright disputes can be carried out through litigation and non-litigation. It would be better for the public to choose to watch legally and subscribe through an official service despite having to pay for the safety and convenience of the user.